2017
DOI: 10.1002/cbdv.201700369
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Involved in Flavonoid Biosynthesis in Sophora japonica Through Transcriptome Sequencing

Abstract: Sophora japonica is a traditional Chinese medicinal ingredient that is widely used in the medicine, food, and industrial dye industries. Since flavonoids are the main components of S. japonica, studying the flavonoid composition and content of this plant is important. This study aimed to identify molecules involved in the flavonoid biosynthetic pathways in S. japonica. Deep sequencing was performed, and 85,877,352 clean reads were filtered from 86,095,152 raw reads. The clean reads were spliced to obtain 111,3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…However, no unigene coding for flavone synthase (FNS) was detected in the transcriptome analysis. A similar situation has been reported in the transcriptome sequencing of other plants such as Sophora japonica, which may be attributed to the fact that FNS genes are short fragments without sequence similarity [23].…”
Section: Cluster and Kegg Enrichment Analysis Of Degssupporting
confidence: 75%
“…However, no unigene coding for flavone synthase (FNS) was detected in the transcriptome analysis. A similar situation has been reported in the transcriptome sequencing of other plants such as Sophora japonica, which may be attributed to the fact that FNS genes are short fragments without sequence similarity [23].…”
Section: Cluster and Kegg Enrichment Analysis Of Degssupporting
confidence: 75%
“…A previous study identified 13 enzyme genes involved in the flavonoid biosynthesis in S . flavescens 29 . In the current study, useful data for investigating the molecular and chemical information of the distribution of alkaloids and flavonoids in S. flavescens are provided.…”
Section: Discussionmentioning
confidence: 99%
“…Liquiritin, the main flavonoid compound in licorice, is synthesized in the cytoplasm via a flavone biosynthetic pathway (Stefan et al., 2011; Zhang et al., 2021) that is controlled and regulated by phenylalanine ammonia‐lyase (PAL), cinnamate 4‐hydroxylase (C4H) and 4‐coumarate CoA ligase (4CL) to form 4‐coumaroyl‐CoA (Zhang et al., 2017). Under the catalysis of chalcone synthase (CHS), 4‐coumaroyl‐CoA is condensed with three molecules of malonyl‐CoA synthesized from acetyl‐CoA by acetyl‐CoA carboxylase (ACC).…”
Section: Introductionmentioning
confidence: 99%